Ecology and Applied Environmental Science - Hadjibiros, Kimon (Taylor & Francis, 2014)
Ecology and Applied Environmental Science addresses the impact of contemporary environmental problems by using the main principles of scientific ecology. It offers a brief yet comprehensive explanation of ecosystems based on energy, populations, and cycles of chemical elements. The book presents a variety of scientific ecological issues and uses these to examine a range of environmental problems while considering potential engineering, scientific, and managerial solutions. It takes an engineering approach and avoids excessive biological detail, while introducing ecology with a systemic approach. The book examines categories of organisms as well as the physical and chemical processes that affect them. It refers to the dynamics of populations and analysis of their major mutual influences, elaborates on the roles of primary production, limiting factors, energy flow, and circulation of chemical substances in the ecosystems, and presents the basic functions of aquatic ecosystems. The author considers important issues related to environmental degradation of forests, aquatic habitats, coastal zones, other natural landscapes, and urban areas, includes a survey of problems related to waste and toxic and radioactive substances, and presents the greenhouse effect and impacts from climate change. He discusses environmental management prospects and the potential for technological control of pollution from liquid, solid, and gaseous waste. He also highlights existing tools for environmental management, ecological and social aspects of biodiversity and landscape protection, and the contrast between development and environment in combination with ideas about sustainability. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license.